Investigating the Factors of Mega Infrastructure Project Delays: : Dhaka Context - Biswas, Abhijit; Hasan, Md. Mehedi (The Jahangirnagar Review, 2024)
Projects are short-term initiative that aim to produce a distinctive advantage, service or outcome, and infrastructure refers to the physical features that use the operation of a company, region, or nation, frequently involving the generation of public goods or the execution of production procedures. Mega infrastructure project, which costs at least 1 billion are a haphazardly organized collection of unconnected components with various uncertainty and unknown challenges. These various uncertainties and unknown challenges cause mega infrastructure project delays. Project delay increases the cost of the project and causes economic loss. For example, Bangladesh is currently running some mega infrastructure projects but facing project delays in some cases resulting financial loss for the government. To be more specific, MRT Line 6 project was selected as a case study that faced delay in completion. In this connection, this study tries to identify the specific reasons causing delays in completing MRT Line-6. This study followed a qualitative research approach to explore the factors through In Vivo Coding in the first cycle of coding and Pattern Coding in the second cycle of coding. Issues of the contractors, lack of knowledge and skills, design changes, low quality of planning and management, material collection, political issues, land acquisition, covid 19, safety and security concerns of foreign workers, traffic pressure in the city, institutional issues are the factors explored in this study that causes the delay of MRT Line 6. The study can contribute to understanding delay factors and applying knowledge for future infrastructure projects, particularly in developing countries, at the same time, it will provide valuable insights for policymakers to make better infrastructure decisions and ensure successful completion of project.